Respiratory microbes detected in hospitalized adults with acute respiratory infections: associations between influenza A(H1N1)pdm09 virus and intensive care unit admission or fatal outcome in Vietnam (2015–2017) - Truong, Phuong Thai; Saito, Shinji; Takayama, Ikuyo; Furuya, Hiroyuki; Nguyen, Binh Gia; Do, Thanh Van; Phan, Phuong Thu; Do, Cuong Duy; Dao, Co Xuan; Pham, Thach The; Dang, Tuan Quoc; Ngo, Chau Quy; et al. (BMC infectious diseases, 2021)
Acute respiratory tract infection (ARI) is a leading cause of hospitalization, morbidity, and mortality worldwide. Respiratory microbes that were simultaneously detected in the respiratory tracts of hospitalized adult ARI patients were investigated. Associations between influenza A(H1N1)pdm09 virus (H1N1pdm) detection and intensive care unit (ICU) admission or fatal outcome were determined. This prospective observational study was conducted between September 2015 and June 2017 at Bach Mai Hospital, Hanoi, Vietnam. Inclusion criteria were hospitalized patients aged ≥15 years; one or more of symptoms including shortness of breath, sore throat, runny nose, headache, and muscle pain/arthralgia in addition to cough and fever > 37.5 °C; and ≤ 10 days from the onset of symptoms. Twenty-two viruses, 11 bacteria, and one fungus in airway specimens were examined using a commercial multiplex real-time PCR assay. Associations between H1N1pdm detection and ICU admission or fatal outcome were investigated by univariate and multivariate logistic regression analyses. The total of 269 patients (57.6% male; median age, 51 years) included 69 ICU patients. One or more microbes were detected in the airways of 214 patients (79.6%). Single and multiple microbes were detected in 41.3 and 38.3% of patients, respectively. Influenza A(H3N2) virus was the most frequently detected (35 cases; 13.0%), followed by H1N1pdm (29 cases; 10.8%). Hematological disease was associated with ICU admission (p < 0.001) and fatal outcomes (p < 0.001) using the corrected significance level (p = 0.0033). Sex, age, duration from onset to sampling, or number of detected microbes were not significantly associated with ICU admission or fatal outcomes. H1N1pdm detection was associated with ICU admission (odds ratio [OR] 3.911; 95% confidence interval [CI] 1.671-9.154) and fatal outcome (OR 5.496; 95% CI 1.814-16.653) after adjusting for the confounding factors of comorbidities, bacteria/Pneumocystis jirovecii co-detection, and age. H1N1pdm was associated with severe morbidity and death in adult patients hospitalized with respiratory symptoms. The diagnosis of subtype of influenza virus may be epidemiologically important.